Pengaruh Faktor Sosial, Faktor Pribadi, Faktor Psikologi, Faktor Kebudayaan terhadap Keputusan Pembelian Kartu Three - Anggreni, Putri (BISMA (Bisnis dan Manajemen), 2018)
Introduction to consumer demand for a product is the beginning of the decision-making process. The need to communicate is a very important thing in human life. With respect to the existence of diverse consumers and their behavior then the management should really responsive to observations of what is wanted. In connection with the research done on the title : The Effect of Social Factors, Personal Factors, Psychological Factors, Cultural Factors Against Three Card Purchase Decision In Singaraja City, based on the results of multiple linear regression analysis was done in this study, obtained the following regression equation: Y = 6.604 + 0.254X1 + 0.494X2 - 0.298X3 + 0.526X4. The results obtained by the analysis of social factors that variable (X1) has a regression coefficient of 0.254 (is positive) to the purchasing decision (Y) and t value of 1.116 with a significance level of 0.275 (> 0.05). This means that social factors (X1) has no significant influence on purchasing decisions (Y). Thus Hypothesis This means that Ho accepted and Ha is rejected, the analysis results obtained that individual factor variables (X2) has a regression coefficient of 0.494 (is positive) to the purchasing decision (Y) and t value of 3.149 with a significance level of 0.004 (> 0.05 ). This means that individual factors (X2) has a significant influence on purchasing decisions (Y). Thus the hypothesis Ho is rejected and Ha accepted, results obtained by analysis of the psychological factors that variable (X3) has a regression coefficient of 0.298 (negative sign) to the purchasing decision (Y) and t value of -0.781 with a significance level of 0.442 (> 0.05). This means that the psychological factor (X3) does not have a significant influence on purchasing decisions (Y). Thus Hypothesis This means that Ho accepted and Ha is rejected, results obtained by analysis of the cultural factors that variable (X4) has a regression coefficient of 0.526 (is positive) to the purchasing decision (Y) and t value of 1.604 with a significance level of 0.121 (> 0.05 ). This means that cultural factors (X4) does not have a significant influence on purchasing decisions (Y). Thus Hypothesis this means that : Ho accepted and Ha is rejected, adjusted R-square value obtained for 0.480 or 48.0%. Than customer satisfaction (Y) can be explained by the variable quality of service (X1), product (X2), promotion (X3), while 52.0% can be explained by factors-factors not examined in this study.